Redescription of Orthocis platensis Brèthes, 1922 (Coleoptera: Ciidae) and the first records of the species from Brazil - Lopes-Andrade, Cristiano; de Araujo, Lucimar Soares; Sandoval-Gómez, Vivian E. (Zootaxa, 2020)
The genus Orthocis Casey is represented by 46 species occurring in insular and continental areas of the World, except for the Antarctic. Three Orthocis species are currently known from South America: the Andean O. elguetai Lopes-Andrade, from Chile; the Neotropical O. apicipennis (Pic) from a single locality in South Brazil; and O. platensis Brèthes from Buenos Aires, Argentina. Orthocis platensis is here redescribed and recorded for the first time from South and Southeast Brazil.